2006
DOI: 10.1152/ajprenal.00063.2006
|View full text |Cite
|
Sign up to set email alerts
|

Claudins 6, 9, and 13 are developmentally expressed renal tight junction proteins

Abstract: The adult proximal tubule is a low-resistance epithelium where there are high rates of both active transcellular and passive paracellular NaCl transport. We have previously demonstrated that the neonatal rabbit and rat proximal tubule have substantively different passive paracellular transport properties than the adult proximal tubule, which results in a maturational change in the paracellular passive flux of ions. Neonatal proximal tubules have a higher PNa/PCl ratio and lower chloride and bicarbonate permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 56 publications
9
95
0
Order By: Relevance
“…36 Inversely, RON proto-oncogene product and S100 protein were found preferentially expressed in oncocytoma warranting further investigation. 37,38 Preclinical studies have demonstrated a developmental expression of claudin isoforms in the renal tissue, 39 and have identified a distinct pattern of expression of isoforms 7 and 8 along the mouse distal nephron. 10 Gene expression profiling studies in humans have proposed in recent years that chromophobe renal cell carcinoma and oncocytoma are distinguishable by mRNA expression profiles and have indicated claudin 7 as one of the candidate markers for chromophobe renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…36 Inversely, RON proto-oncogene product and S100 protein were found preferentially expressed in oncocytoma warranting further investigation. 37,38 Preclinical studies have demonstrated a developmental expression of claudin isoforms in the renal tissue, 39 and have identified a distinct pattern of expression of isoforms 7 and 8 along the mouse distal nephron. 10 Gene expression profiling studies in humans have proposed in recent years that chromophobe renal cell carcinoma and oncocytoma are distinguishable by mRNA expression profiles and have indicated claudin 7 as one of the candidate markers for chromophobe renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This would indicate that cldn-6 may play a role in the physiology of the blood-brain barrier in fishes or other processes in the nervous tissue. In contrast, cldn-6 is absent from most adult mammalian tissues (including the brain) and its expression has been associated with prenatal developmental stages (Abuazza et al, 2006;Fujita et al, 2006;Morita et al, 1999;Morita et al, 2002;Reyes et al, 2002;Turksen and Troy, 2001;Turksen and Troy, 2002). Nevertheless, in adult mammalian tissues, Cldn-6 has been reported in the kidney (Morita et al, 1999;Zhao et al, 2008), taste buds (Michlig et al, 2007) and mammary gland (Quan and Lu, 2003), and in embryos and neonates, cldn-6 has been found in a variety of tissues that include the kidney (Zhao et al, 2008), the periderm of -ATPase (NKA; green) and (B) Cldn-6 (red) immunoreactivity show (C) colocalization of these proteins in ionocytes (arrowheads) with some peripheral punctate Cldn-6 staining around ionocytes (arrows).…”
Section: Discussion Overviewmentioning
confidence: 99%
“…Cldn 3 transcripts and protein were expressed in the developing mouse metanephric kidney, and overexpression of Cldn3 in in vitro model of kidney tubule formation promoted tubulogenesis (Haddad et al, 2011). Claudin 16 and Claudin 9 expression was observed in mouse embryonic and neonatal kidney (Abuazza et al, 2006, Khairallah et al, 2014. Additionally, Cldn16 knockout mice and humans with mutations in Cldn16 gene exhibit kidney disease (Gupta and Ryan, 2010).…”
Section: Fig 11 Loss Of Claudin 3b Results In Pharyngeal Arch and Omentioning
confidence: 99%